Relevansi Wakaf Produktif dalam Upaya Optimalisasi Pendayagunaan Wakaf bagi Kemaslahatan Umat - Abdur Rohman; Bahrul Ulum (Comprehensive Journal of Islamic Studies, 2025)
Waqf is one of the pillars of the Islamic economic system that plays an important role in creating social welfare and empowering the community. Despite its great potential, the practice of managing waqf assets in Indonesia tends to be conventional and less productive, with limited utilization in places of worship such as mosques and madrasas. The concept of productive waqf is present as an innovative alternative that allows waqf assets to be managed more dynamically for value-added economic activities. Through this approach, waqf assets not only maintain spiritual value, but also contribute to improving the economic welfare of the community more broadly and sustainably. This study aims to examine the urgency of implementing productive waqf in optimizing waqf assets, while identifying various challenges and opportunities in its implementation. In implementing this research, a literature review method with a qualitative approach was used. The results of the study indicate that productive waqf has a large capacity in driving the economic sector of the community, as long as it is supported by a professional, transparent, and accountable management system. With proper governance, productive waqf can be a strategic instrument in the development of an inclusive and equitable Islamic economy.